2017
DOI: 10.4103/ijc.ijc_202_17
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of immunohistochemistry and fluorescent in situ hybridization assay to detect anaplastic lymphoma kinase status in lung adenocarcinoma cases: A search for a testing algorithm

Abstract: A negative ALK IHC result obviates the need for a FISH test barring those with a strong clinical profile, and a positive ALK IHC result is sufficient basis for the initiation of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…More recent studies on D5F3 IHC using a binary scoring algorithm have reported 100% sensitivity and high specificities. 63 , 65 …”
Section: Ihc With D5f3mentioning
confidence: 99%
“…More recent studies on D5F3 IHC using a binary scoring algorithm have reported 100% sensitivity and high specificities. 63 , 65 …”
Section: Ihc With D5f3mentioning
confidence: 99%